MARKETING RESEARCHES OF THE POPULATIONS HEALTH STATE AS A FACTOR OF DEMAND FORMATION IN THE MARKET OF PAID MEDICAL SERVICES - Hrechanyk , N.Yu.; Sarabyn , T.M. (The actual problems of regional economy development, 2017)
The state of health of the population is one of the most important indicators of the well-being of the nation. Important directions of health care reform are optimization of management, rational distribution of limited financial resources, efficient use of material resources, introduction of health insurance, restructuring of treatment and preventive care to the people. Marketing of medical services market is one of the most complex types of marketing. Because it is medical services that are connected with the protection and maintenance of the most important values ​​of a person - life and health. The market for medical services is a combination of socio-economic relations in the healthcare sector. The most important components of the analysis of any market, including the market of medical services, are marketing research, which is a systematic collection, processing, analysis of data and information in order to formulate proposals for effective activities on it. In the field of public health, marketing can be defined as a complex process of planning, economic substantiation and management of the process of provision of medical services, the formation of a pricing policy of the medical-preventive process, ensuring effective communication with patients. The purpose of the study is to identify the health of the population and determine the demand factors for paid health services and their demand. The main task set before market research on the health of the population is the formation and provision of benefits to consumers that meet their needs for qualified medical care and quality of life. The research methods used in the work are based on probabilistic, stratified, quota, representative samples for the entire population of Ivano-Frankivsk and Ivano-Frankivsk region. The obtained results allow us to give a realistic assessment of the main trends and allow us to assess the potential of socio-economic adaptation of the population in the conditions of the economic crisis, as well as practical application in the practice of the «Oxford Medical Center “Prykarpattya”.